How schools in England understand and enact education policy: the case of modern languages at key stage 4 - Hagger-Vaughan, Lesley (2018)
Whilst learning an additional language throughout compulsory schooling is increasingly the norm across the world, this is not the case in England, where currently fewer than 50% of young people study a modern language at upper secondary level (key stage 4). However, a recent change to education policy has required the ‘vast majority’ of young people to study a language to GCSE level as part of the combination of subjects which form the English Baccalaureate (EBacc) performance measure. This research explores the interrelated nature of the factors that help and hinder schools in responding to this policy requirement to extend participation in language learning.